COMPETENCE BASED TRAINING IMPLEMENTATION PRINCIPLES - Pitor, Jan; Havel, Karel (Doprava a spoje, 2012)
This paper summarizes the basic principles of competence based training implementation into pilot training. It provides an overview of competence based training features, defines the term "competency" and shows the differences of assessment in comparison to conventional types of training. At the end it shows some problems that may be encountered during competence based training construction.